Teacher Training in Nepal: Issues and Challenges - Gautam, Ganga Ram (Tribhuvan University Journal, 2016)
“No single element is more essential to students’ success than excellence in teaching. Fine buildings, equipment, and textbooks are important, but it is the skill and dedication of the teacher that creates a place of learning.” (Hickok, E. 1998). The quote highlights the role of teachers and it is generally accepted that teachers are the key actors who contribute to the making of people through education. Teachers are often considered as ‘good people’ and in the context of Nepal especially in the rural areas; it is the teacher who is often consulted for any important work in the community. “The teachers are in the business of making good people, or of enabling their students to become good people. They do this specifically by helping them to become smarter” (Tate, 2007: 1). Thus, preparation of teaching force is, therefore, a key concern of the government throughout the world. It is the teacher who lays the foundation of all the professionals when they attend the elementary and secondary school (Farris and Rieman, 2014). Nepal government too has invested a huge amount of resources in teacher training thinking that training would result effective pedagogic skills among teachers and they could then use those skills in their classrooms so that students will have better achievement. However, while reviewing the available literature on teacher training in Nepal, it shows that very little has been achieved in this area in the last few decades. This article is an attempt to review the impact of teacher training in Nepal and identify the major issues in them so as to find out the ways of improving the teacher training in Nepal.